Development of a broadband cavity-enhanced absorption spectrometer for simultaneous measurements of ambient NO3, NO2, and H2O - W. Nam; C. Cho; B. Perdigones; T. S. Rhee; K.-E. Min (Atmospheric Measurement Techniques, 2022)
We describe the characteristics and performances of our newly built broadband cavity-enhanced absorption spectrometer for measurements of nitrate radical (NO3), nitrogen dioxide (NO2), and water vapor (H2O). A customized vibration-resistance cavity layout incorporated with N2 purging on high-reflection mirror surfaces was implemented with a red light-emitting diode (LED) as a light source. In general, this system achieved over 40 km (up to 101.5 km) of effective light path length at 662 nm from a 0.52 m long cavity. For accurate NO3 measurement, the measured absorption spectrum of H2O was used for simultaneous concentration retrievals with the other species instead of being treated as interferences to be removed or corrected prior to NO3 detection. Synthesized N2O5 crystals under atmospheric pressure were used for performance tests of linear response and transmission efficiency. From the standard injection experiments of NO3, NO2, and H2O, high linearities were observed (R2≥0.9918). The total NO3 transmission efficiency through the system was determined to be 81.2 % (±2.9, 1σ) within the residence time of 2.59 s. The precisions (1σ) of NO3, NO2, and H2O in 1 Hz measurement from a single pixel on the charge-coupled device (CCD) were 1.41 pptv, 6.92 ppbv, and 35.0 ppmv with uncertainties of 10.8 %, 5.2 %, and ≥20.5 %, respectively, mainly from the errors in the literature absorption cross-section. The instrument was successfully deployed aboard the Korean icebreaker R/V Araon for an expedition conducted in the remote marine boundary layer in the Arctic Ocean during the summer of 2021.